PENGARUH KONSEP DIRI, PERAN INTERAKSI EDUKATIF ORANG TUA DAN KECERDASAN EMOSIONAL TERHADAP KEMANDIRIAN BELAJAR MAHASISWA JURUSAN TADRIS MATEMATIKA IAIN PADANGSIDIMPUAN - ALMIRA AMIR (Institut Agama Islam Negeri Padangsidimpuan, 2015)
The problem in this study is whether the self-concept, role of educational interaction of parents, and emotional intelligence provides a positive and significant influence on the independence of student learning in Tadris Matematika Padangsidimpuan IAIN either separately or simultaneously. The population in this study were all students of mathematics at IAIN Padangsidimpuan Tadris totaling 520 students. The sampling technique in this research is to use a simple random sampling technique. Data collection instruments used is by using questionnaires. Test the validity of the questionnaire item analysis using product moment correlation formula, reliability calculated using Cronbach Alpha. The data analysis technique used is the technique of multiple linear regression analysis, t test and F test.Self-concept variables (X1) positive and significant impact on student learning independence by using the t test is tcount ttable or 7.778 1.987. Similarly, the role of educational interaction variables parents (X2), the result is also stated that there is a positive and significant influence on the independence of student learning using the t test is tcount ttable or 4.869 1.987. Similarly, emotional intelligence variable (X3), the variable is also stated there was a positive and significant influence on the independence of student learning using the t test is tcount ttable or 8.613 1.987. Simultaneously any self-concept variables (X1), the role of educational interaction of parents (X2), and emotional intelligence (X3) positive and significant impact on the independence of the variables studied mathematics majors at IAIN Tadris Padangsidimpuan (Y) using the F test is Fcount Ftable or 37.359 2.704. Student learning independence can be explained by the independent variables of 0,539 or 53.9%.